Removal of Group B Streptococci Colonizing the Vagina and Oropharynx of Mice with a Bacteriophage Lytic Enzyme - Cheng, Qi (American Society for Microbiology, 2005)
Group B streptococci (GBS) are the leading cause of neonatal meningitis and sepsis worldwide. The current treatment strategy is limited to intrapartum antibiotic prophylaxis in pregnant women to prevent early-onset neonatal diseases, but considering the potential for antibiotic resistance, the risk of losing control over the disease is high. To approach this problem, we have developed a bacteriophage (phage) lytic enzyme to remove colonizing GBS. Bacteriophage muralytic enzymes, termed lysins, are highly evolved molecules designed to degrade the cell wall of host bacteria to release phage particles from the bacterial cytoplasm. Several different lysins have been developed to specifically kill bacterial pathogens both on mucosal surfaces and in blood and represent a novel approach to control infection. A lysin cloned from a phage infecting GBS was found to contain two putative catalytic domains and one putative binding domain, which is similar to the domain organization of some staphylococcal phage lysins. The lysin (named PlyGBS) was recombinantly expressed in Escherichia coli, and purified PlyGBS efficiently killed all tested GBS serotypes in vitro. In a mouse model, a single dose of PlyGBS significantly reduced bacterial colonization in both the vagina and oropharynx. As an alternative strategy for intrapartum antibiotic prophylaxis, this approach may be used to reduce vaginal GBS colonization in pregnant women before delivery or to decontaminate newborns, thus reducing the incidence of GBS-associated neonatal meningitis and sepsis.